Ivermectin adsorption by commercial charcoal in batch and fixed-bed operations (2023)
Emerging contaminants were used during the COVID-19 pandemic, including ivermectin. Studies that limit the optimal adsorption parameters of ivermectin are scarce in the literature. In this study, we analyzed the adsorption of ivermectin with a high surface area and porosity charcoal. Isotherms were better fitted to the Koble-Corrigan model. The maximum capacity was 203 μg g−1 at 328 K. Thermodynamics indicated a spontaneous and endothermic behavior. The equilibrium was quickly reached within the first few minutes regardless of the ivermectin concentration. The linear driving force (LDF) model fitted the kinetic data (qexp = 164.8 μg g−1; qpred = 148.1 μg g−1) at 100 μg L−1 of ivermectin. The model coefficient (KLDF) and diffusivity (Ds) increased with increasing drug concentration. Two sloped curves were obtained in the column experiments, with a breakthrough time of 415 min and 970 min. The capacity of the column (qeq) was 76 μg g−1. The length of the mass transfer zone was 9.04 and 14.13 cm. Therefore, it can be concluded that the adsorption of ivermectin is highly sensitive to changes in pH, being favored in conditions close to neutrality. Commercial activated charcoal was highly efficient in removing the studied compound showing high affinity with very fast kinetics and a good performance in continuous operation mode